(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
In recent years, the rapidly growing industry has also harmed aquatic life due to water pollution, especially heavy metal pollution. Herein, the CoxFe3-xO4/ZnO/activated carbon (AC) nanocomposite was synthesized via the coprecipitation and sol–gel methods to apply as a copper adsorbent. X-ray diffractometry revealed the cubic spinel crystal structure of CoxFe3-xO4 and the hexagonal wurtzite structure of ZnO. Examination under scanning electron microscopy depicted the morphology of the samples as comprising spheres, sheets, and chunks. The spherical nanoparticles exhibited an average particle size of 45.08–65.36 nm. Fourier transform infrared spectra confirmed the presence of all components within the nanocomposite, including CoxFe3-xO4, ZnO, and AC. Analysis using a vibrating sample magnetometer indicated the superparamagnetic nature of the nanocomposite, 11.069–23.514 emu/g with magnetic saturation value. To assess the influence of Co composition, adsorption experiments were conducted with varying contact time intervals. Remarkably, these experiments demonstrated the copper removal efficiencies of samples S1-S4 was 9969%, 99.86%, 99.76% and 99.92%, respectively, while the best copper removal efficiency of 99.96% was achieved by sample S5, with 11.00 mg/g maximum adsorption capacity. Thus, the CoxFe3-xO4/ZnO/AC nanocomposite demonstrates significant potential as a novel material for copper removal in adsorption applications.